2004
DOI: 10.1890/03-5009
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale Experiments Support Causal Relationships Between Metal Contamination and Macroinvertebrate Community Responses

Abstract: Routine biomonitoring studies that compare abundance of benthic macroinvertebrates upstream and downstream from contaminant discharges generally cannot be used to demonstrate causal relationships between stressors and biological responses. In this study I describe stream microcosm and field experiments designed to support results of a 12-year monitoring project in the metal-polluted Arkansas River, Colorado. Microcosm experiments established concentration-response relationships between heavy metals and several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
141
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 57 publications
14
141
2
1
Order By: Relevance
“…Our studies identified the genus Ephemerella and two heptanegiid mayflies as being particularly susceptible to dissolved Cd. These findings give mechanistic support to observations that these taxa are consistently absent from metal-contaminated habitats in nature (40) and are consistently more sensitive to metals in sophisticated toxicity tests (39)(40)(41). The presence of a relatively strong phylogenetic signal associated with the integrated trait of ''sensitivity to dissolved Cd'' suggests that sensitivity to metals may eventually be predictable on the basis of phylogenetic position, as described above.…”
Section: Discussionsupporting
confidence: 78%
“…Our studies identified the genus Ephemerella and two heptanegiid mayflies as being particularly susceptible to dissolved Cd. These findings give mechanistic support to observations that these taxa are consistently absent from metal-contaminated habitats in nature (40) and are consistently more sensitive to metals in sophisticated toxicity tests (39)(40)(41). The presence of a relatively strong phylogenetic signal associated with the integrated trait of ''sensitivity to dissolved Cd'' suggests that sensitivity to metals may eventually be predictable on the basis of phylogenetic position, as described above.…”
Section: Discussionsupporting
confidence: 78%
“…The present study used metrics of invertebrate taxa richness which are generally considered to be sensitive indicators of metal pollution (Hickey andClements, 1998 andClements, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to heavy metals in the Arkansas River has significantly altered composition of benthic macroinvertebrate communities (Clements 2004). Although the Arkansas River system is open to immigration from non-polluted sites such as the West Tennessee Creek, there are differences in the occurrence of metaltolerant and metal-sensitive species between sites.…”
Section: Discussionmentioning
confidence: 99%